Analisis Faktor Yang Berhubungan Dengan Keikutsertaan Tes Iva Pada Ibu Yang Datang Di Puskesmas Biru-Biru Pada Masa Pandemi Covid-19 Tahun 2022 - Halawa, Kris Angelina (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Cervical cancer is the cause of death for 90% of women in developing countries. The incidence of cervical cancer can be prevented by early detection, one of which is the VIA examination. During the current Covid-19 pandemic, one of the efforts that health workers can take to reduce the risk of cervical cancer is to carry out early detection of female reproductive organs through an VIA examination. Based on the list of service visits during the COVID-19 pandemic, the achievement of the IVA examination carried out in the Puskesmas Biru-biru area was far from the target. The purpose of this study was to determine the factors related to participation in the IVA test for mothers who came to the Puskesmas Biru-biru during the Covid-19 pandemic. This type of research is quantitative with a cross-sectional design. The research subjects were mothers who came to the Puskesmas Biru-biru while the researchers came to the Puskesmas Biru-biru during the research period from March-April until 100 respondents were met. The results showed that there were 2 factors related to the participation of the IVA test on the mother, namely: attitude (p = 0.000) and husband's support (p = 0.002). There were 5 factors that were not related to the participation of the IVA test on mothers, namely: age (p = 0.604), education (p = 0.997), knowledge (p = 0.128), support from health workers (p = 0.395) and motivation (p = 0.867). The most dominant variable associated with maternal IVA test participation was attitude with a PR value of 7.08 (95% CI; 2.70-18.52) and a value of 0.000. This means that mothers with a supportive attitude are 7.08 times more likely to take the IVA test compared to mothers with a non-supportive attitude.